Malicious User Attack in Cognitive Radio Networks - N. Armi; S. Rizvi; W.Z. Khan; H. Zangoti; W. Gharibi; C. Wael (Universitas Ahmad Dahlan, 2017)
Signal detection in cognitive radio network (CRN) is influenced by several factors. One of them is malicious user that emulate primary user (PU) signal. Emulation of PU signal causes detection error. This paper investigates the impact of malicious user attack to PU signal detection. A number of malicious users are randomly deployed around secondary user (SU) at a certain distance. They attempt to attack primary signal detection that is transmitted from 100 km to SU receiver. Then, the received signal power at secondary receiver and the performance of probability of false alarm and probability of miss detection under two hypothesis of Neyman Pearson criterion are studied. The derived results show that a number of malicious users has a significant impact to the performance of received power at SU and detection error rate.